The Effectiveness of Applying Intonation in Communication with Individuals with Neutral Disabilities - Esra Anggriani Br. Hutabarat; Amelia Chamila (Jurnal Multidisiplin Sahombu, 2026)
Effective communication for individuals with visual disabilities relies heavily on auditory cues, particularly intonation, to convey meaning, emotion, and pragmatic intent. This study explores the effectiveness of applying intonation patterns in verbal communication with persons with visual impairments. The article emphasizes intonation as a suprasegmental element that supports message clarity, emotional recognition, and interactional flow when visual information is unavailable. Through an integrative qualitative approach grounded in relevant linguistic and communication studies, this paper examines how variations in pitch, stress, rhythm, and tempo influence comprehension and engagement among visually disabled individuals across different communicative contexts. The findings highlight that appropriate intonation enhances understanding, reduces ambiguity, and fosters more inclusive and empathetic interactions. Moreover, effective intonation use contributes to greater communicative confidence and social participation for individuals with visual disabilities. The study underscores the importance of intonation awareness for educators, caregivers, and the general public in promoting accessible and human centered communication practices.